Theory of Mind (ToM) Development in Thai Deaf Children. (30th December 2020) - Siriattakul, Parinya; Suttiwan, Panrapee; Slaughter, Virginia; Peterson, Candida C
Abstract: This study explored theory of mind (ToM) development in school-aged deaf children. To address new questions, we gave a standard, well-controlled false-belief test to a large ( n = 200) sample of severely-to-profoundly deaf children aged 8–15 years in a non-Western culture (Thailand). There were 190 deaf children of hearing parents and 10 deaf native signers with signing deaf parents, consistent with overall population ratios. Comparing our Thai sample's ToM performance on standard tests of false-belief understanding with that reported in past studies, our results showed a 67% ToM success rate for Thai severely-to-profoundly deaf children of hearing parents similar to collective findings from past research on smaller samples in Australia, Estonia, France, Great Britain, Sweden, and the United States. Our Thai deaf native signers likewise performed equivalently to native signers of similar age studied in past research in Australia and the United States. Collectively, the detailed findings of our study suggest promising new directions for future studies to pursue in order to build upon this novel and theoretically provocative evidence about how ToM development and ToM delay unfold for school-aged deaf children growing up in varied cultures, school settings, and family circumstances.